Infection in pregnancy; understanding impact on placental microenvironment and preterm birth: a review (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Background: Pregnancy increases susceptibility to and severity of infections caused by certain microbes and  parasites. The presence of these infectious agents at the maternofetal interface may lead to adverse pregnancy  outcomes including preterm birth either via direct action of the microbes or indirectly via alteration of the placental  microenvironment. Objective: To summarize the literature regarding the role of various infectious agents in alteration of placental  microenvironment and predisposition to preterm birth.  Method: A review search using Google scholar, PubMed, Cochrane Library and Trip database was conducted at the  University of California San Francisco. A total of 880 abstracts were reviewed and a total of 95 studies were included.  Studies were included if they reported any information on infection during pregnancy, effect on placenta or fetal  membranes or risk of preterm birth. Results: The current evidence indicates that various infectious agents affect pregnancy and alter placental  microenvironment at the maternofetal interface. Severity of these infections increases with gestation. Additionally,  these infections are associated with the risk of adverse obstetric outcomes including preterm birth.  Conclusion: Prevention, early detection and treatment of these infections including those that are asymptomatic is  important in maintaining integrity of the placenta and in reducing the burden of preterm births.